KANTOR DIGITAL KREATIF STARTUP - Timothy Timothy; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
In this industrial revolution 4.0 era, digital technology has become a necessity for millennials. Through the internet, everyone can be connected to each other making it a new business opportunity, namely startup. The presence of a startup business based on digital business is now a trend among millennials. However, building a startup business is not easy. Many startup businesses that are falling apart in running their businesses are even unable to compete with larger startup. Offices with old systems are no longer in accordance with millennial behaviors and this startup business needs more creative and innovative ideas. Millennials need a place to work with new concepts in increasing their creativity and productivity at work. The proposed program 'Creative Startup Digital Office' aims to present an office program with a new concept for millennials in running a startup business in today's digital era. The office is no longer just a place to work but a place to find experience, learn new things, socialize and community. Millennial requires an interactive, relaxed, fun, flexible and collaborative work environment to support productivity performance in the office. With the presence of this startup office, it is hoped that it will be able to improve the economy of the people especially millenials  in entrepreneurship through a growing startup business.          AbstrakDi era revolusi industri 4.0, teknologi digital sudah menjadi kebutuhan bagi para milenial. Melalui internet semua bisa saling terhubung satu dengan yang lain menjadikannya sebuah peluang bisnis baru yaitu startup. Kehadiran startup bisnis yang berbasis bisnis digital ini sekarang menjadi trend bisnis di kalangan milenial. Akan tetapi, membangun sebuah bisnis startup tidaklah mudah. Banyak bisnis startup yang jatuh bangun dalam menjalankan bisnisnya bahkan kalah bersaing dengan startup yang lebih besar. Kantor dengan sistem lama tidaklah sesuai dengan perilaku milenial dan bisnis startup ini yang lebih banyak membutuhkan ide-ide kreatif dan inovatif. Para milenial membutuhkan sebuah tempat bekerja dengan konsep baru dalam meningkatkan kreatifitas dan produktivitas mereka dalam bekerja. Pengusulan program “Kantor Digital Kreatif Startup” memiliki tujuan untuk menghadirkan program kantor dengan konsep yang baru untuk para milenial dalam menjalankan bisnis startup di era serba digital saat ini. Kantor bukan lagi sebagai tempat untuk bekerja saja melainkan tempat untuk mencari pengalaman, belajar hal baru, bersosialisasi dan berkomunitas. Milenial membutuhkan lingkungan kerja yang interaktif, santai, menyenangkan, fleksibel dan kolaboratif untuk mendukung performa produktivitas di dalam kantor. Dengan hadirnya kantor startup, diharapkan dapat meningkatkan perekonomian masyarakat terutama kaum milenial dalam berwirausaha melalui bisnis startup yang sedang berkembang.